Regulatory T Cell Modulation by Lactobacillus rhamnosus Improves Feather Damage in Chickens - Mindus, Claire; van Staaveren, Nienke; Fuchs, Dietmar; Gostner, Johanna M.; Kjaer, Joergen B.; Kunze, Wolfgang; Mian, M. Firoz; Shoveller, Anna K.; Forsythe, Paul; Harlander-Matauschek, Alexandra (Frontiers in Veterinary Science, 2022)
It is currently unclear whether potential probiotics such as lactic acid bacteria could affect behavioral problems in birds. To this end, we assessed whether a supplementation of Lactobacillus rhamnosus JB-1 can reduce stress-induced severe feather pecking (SFP), feather damage and fearfulness in adult birds kept for egg laying. In parallel, we assessed SFP genotypic and phenotypic-related immune responses and aromatic amino acid status linked to neurotransmitter production. Social stress aggravated plumage damage while L. rhamnosus treatment improved the birds’ feather cover in non-stressed birds, but did not impact fearfulness. Our data demonstrate the significant impact of L. rhamnosus supplementation on the immune system. L. rhamnosus supplementation induced immunosuppressive regulatory T cells and cytotoxic T cells in both the cecal tonsils and the spleen. Birds exhibiting the SFP phenotype possessed lower levels of cecal tonsils regulatory T cells, splenic T helper cells and a lower TRP:(PHE+TYR). Together, these results suggest that bacteria may have beneficial effects on the avian immune response and may be useful therapeutic adjuncts to counteract SFP and plumage damage, thus increasing animal health and welfare.